Microsimulation modelling of the National Childcare Scheme: Updated cost estimates using SWITCH - Tim Callan; Claire Keane; Mark Regan (The Economic and Social Research Institute (ESRI), 2021)
We use SWITCH, the ESRI's tax-benefit model to simulate the scale, cost and distributive impact of the National Childcare Scheme. The paper provides updates to such estimates these authors produced in 2017, when the scheme was in its naissance. We estimate, that under the current parameters, the scheme will cost just under exteuro180 million and will offer reduced childcare costs to 144,000 children. This cash transfer will be of most benefit to families in the bottom third of the income distribution, with the poorest families seeing income rises of 0.7 per cent. This largely progressive profile is attributable to the means-tested nature of the scheme. We bound our estimates by also allowing informal childminders avail of the scheme - this increases the cost and scale of the scheme noticeably. We also highlight, that as is the case with any subsidy, the incidence may not fully be felt by households. Future research ought to examine how the price structure of childcare facilities adapted in response to this new streamlined scheme.
Keywords: 330